Lifetime prevalence and age-of-onset of mental disorders in adults from the Argentinean Study of Mental Health Epidemiology - Cía, Alfredo H. (2018)
Purpose: Although the Global Burden of Disease Study estimated that depressive disorders and anxiety disorders are the second and fifth leading causes of disability in Argentina, these estimates were based on imputations rather than epidemiological data. The policy implications of these results for the necessary expansion of mental health services in Argentina are sufficiently great that more direct estimates of the population burdens of common mental disorders are needed. Therefore, the purpose is to present the first results regarding lifetime prevalence, projected lifetime risk up to age 75, age-of-onset, cohort effects and socio-demographic correlates of DSM-IV mental disorders among adults (18+) from the general population of urban areas of Argentina. Method: A multistage clustered area probability household survey was administered to 3927 individuals using the World Mental Health Composite International Diagnostic Interview. Results: Lifetime prevalence of any disorder was 29.1% and projected lifetime risk at age 75 was 37.1%. Median age-of-onset of any disorder was 20 years of age. Disorders with highest lifetime prevalence were major depressive disorder (8.7%), alcohol abuse (8.1%), and specific phobia (6.8%). Anxiety disorders were the most prevalent group of disorder (16.4%) followed by mood (12.3%), substance (10.4%), and disruptive behavior disorders (2.5%). Women had greater odds of anxiety and mood disorders; men had greater odds of substance disorders. Age-at-interview was inversely associated with lifetime risk of any disorder. Discussion: The results provide direct evidence for high lifetime societal burdens of common mental disorders in Argentina due to a combination of high prevalence and early age-of-onset.